Medical and psychological support of elderly patients with chronic pain syndrome with emotional and cognitive disorders - Савчук, Вікторія (Psychosomatic Medicine and General Practice, 2021)
This review presents data on the current state of such a problem as the peculiarities of medical and psychological support of elderly patients suffering from chronic pain syndrome and having accompanying emotional and cognitive disorders. Modern recommendations on the tactics of managing patients with chronic pain syndrome, taking into account the psycho-emotional and cognitive sphere of the individual, are highlighted. A review and analysis of the literature over the last 10 years (meta-analyses, randomized clinical trials, observational studies, clinical cases, etc.) was performed using PubMed and Google Scholar. A review and analysis of the literature over the last 10 years (meta-analyses, randomized clinical trials, observational studies, clinical cases, etc.) was performed using PubMed and Google Scholar.